Emil Theodor Kocher: an innovator surgeon. (Colombia Medica, 2009)
Emil Theodor Kocher is considered along with Frank Lahey, Theodor Billroth, William Halsted, Charles Mayo, George Crile and Thomas Dunhill as one of the «Magnificent Seven», referring to the group of surgeons who managed thyroidectomy to make it a safe and efficient intervention that it is now practiced throughout the world. He was author of numerous contributions towards medicine. One of his most important contributions was to elucidate the function of the thyroid gland, through the observation and study of thyroidectomyzed patients, for which he was recognized by the academic and scientific community during the early twentieth century.